If x = 2 + 2 1 / 3 + 2 2 / 3 , find the value of x 3 − 6 x 2 + 6 x − 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
x = 2 + 2 3 1 + 2 3 2 ,
x = 2 3 1 ( 1 + 2 3 2 + 2 3 1 )
x = 2 3 1 ( 2 + 2 3 2 + 2 3 1 − 1 )
x = 2 1 3 1 ( x − 1 )
cubing on both the sides
x 3 = 2 ( x 3 − 3 x 2 + 3 x − 1 )
x 3 − 6 x 2 + 6 x − 2 = 0
Problem Loading...
Note Loading...
Set Loading...
x=2+2^1/3+2^2/3
bringing 2 on L.H.S and cubing on b.s
(x-2)^3=(2^1/3+2^2/3)^3
expanding.......... x^3-8-6x(x-2)=2+4+6(2^1/3+2^2/3)
but 2^1/3+2^2/3=x-2.........from the first step
therefore R.H.S=2+4+6(x-2)=6+6x-12
hence x^3-6x^2+6x=6+6x-12
finally x^3-6x^2+6x-2=0
Therefore answer is 0